1976
DOI: 10.1007/bf00454268
|View full text |Cite
|
Sign up to set email alerts
|

Intensity and rate functions of cochlear and brainstem evoked responses to click stimuli in man

Abstract: The complex of five waves, which are the responses to click stimuli of the auditory nerve and the brainstem auditory nuclei, were recorded in ten human subjects by means of earlobe and scalp electrodes. The rate of the stimuli was varied from 5/s to 80/s and their intensity was varied over a 70 dB intensity range in order to study the rate and intensity functions of each of the response components. With increasing click intensity, the amplitude of the first wave (generated by the auditory nerve) increased prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(46 citation statements)
references
References 25 publications
7
39
0
Order By: Relevance
“…Waves I and II did not show a significant latency differ ence between single-and paired-click stimulation (PCI 4.0 and 1.5 ms). These findings in MS patients are simi lar to those in normal subjects [4,13]. Comparing the responses to paired stimulation with a PCI of 1.5 and 4 ms, wave III was only significantly delayed with a PCI of 1.5 ms [4] in normal subjects.…”
Section: Discussionsupporting
confidence: 61%
“…Waves I and II did not show a significant latency differ ence between single-and paired-click stimulation (PCI 4.0 and 1.5 ms). These findings in MS patients are simi lar to those in normal subjects [4,13]. Comparing the responses to paired stimulation with a PCI of 1.5 and 4 ms, wave III was only significantly delayed with a PCI of 1.5 ms [4] in normal subjects.…”
Section: Discussionsupporting
confidence: 61%
“…The amplitudes of waves I (32 and 99 kHz) and II (32 kHz) became larger as the stimulus intensity was increased from 50 to 70 dB pe SPL, and then decreased as the stimulus intensity was further raised from 70 to 100 dB pe SPL. It has also been reported that wave amplitudes are rarely influenced by intensity changes or decreased as the stimulus intensity was increased because of the saturation of the response [7,36].…”
Section: Effects Of Stimulus Intensitymentioning
confidence: 96%
“…The prolongation of BAEP latencies with progressive decreases in stimulus intensity have previously been observed in response to click stimuli in various laboratory animals and in humans [18,39]. The range of latency increase per decibel (dB) was approximately 6-14 µsec/dB in common marmosets, whereas it was the 8-18 µsec/dB in rats [5,10], 8-28 µsec/dB in dogs [37], 12-53 µsec/dB in monkeys [35], and 35-56 µsec/dB in humans [16,18,36]. The reason why common marmosets have a shorter range of latency increase per dB may be the result of stimulation at higher click frequencies.…”
Section: Effects Of Stimulus Intensitymentioning
confidence: 99%
“…However, the absolute latency of an ABR wave may vary as a function of stimulus intensity (Pratt and Sohmer 1976), stimulus repetition rate (Hyde et al 1976, Pratt and and stimulus frequency (Brama and Sohmer 1977). In addition, a conductive hearing-loss also gives rise to increased absolute response latencies (Sohmer and Cohen 1976).…”
mentioning
confidence: 99%